2020
DOI: 10.5001/omj.2020.115
|View full text |Cite
|
Sign up to set email alerts
|

Family Functional-based Coaching Program on Healthy Behavior for Glycemic Control among Indonesian Communities: A Quasi-experimental Study

Abstract: Objectives This study sought to examine the impact of a family functional-based coaching program on improving the perceived family functioning practice and clinical outcomes among patients with glycemic uncontrolled type 2 diabetes mellitus (T2DM) in the Indonesian community. Methods We applied a quasi-experimental study, pretest, and posttest design with a non-equivalent control group. Sixty pairs of T2DM patient-caretaker dyads were recruited and assigned to either an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The average decrease before and after prolanic gymnastics was 14,625 mg/dl (22). Another study also explained the positive effect of exercise on blood glucose level (23)(24) The current study showed acupressure and creative exercise for 4 weeks with a duration of 3 times a week effectively reduces fasting blood sugar levels in people with type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 56%
“…The average decrease before and after prolanic gymnastics was 14,625 mg/dl (22). Another study also explained the positive effect of exercise on blood glucose level (23)(24) The current study showed acupressure and creative exercise for 4 weeks with a duration of 3 times a week effectively reduces fasting blood sugar levels in people with type II diabetes mellitus.…”
Section: Discussionmentioning
confidence: 56%
“…Another study also confirmed that lack of knowledge and skill among PHNs could impact on quality of health care services [13,14]. Some evidence DOI 10.18502/kls.v7i2.10287 also reported that sufficient knowledge on diabetes management was associated with perceived barriers in blood glucose monitoring [15], and medication adherence [16].…”
Section: Discussionmentioning
confidence: 73%
“…A study was conducted by Jin et al mentioned that a regular monitoring from PHN until patients return home could improve patients' recovery [21]. In addition, other studies revealed that effective monitoring could reduce the occurrence of complications and secondary diseases due to diabetes mellitus [16,26].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study entitled: ‘Family functional-based coaching program on healthy behavior for glycemic control among Indonesian communities: a quasi-experimental study’ published in the September 2020 issue of the Oman Medical Journal . 1 The study has comprehensively evaluated the ameliorative effects of family functional-based mentoring on diabetes mellitus (DM) patients. Herein, we comment on the methodological advancements and limitations that may augment the conduction of experiments of this genre in the future.…”
Section: Dear Editormentioning
confidence: 99%